2021
DOI: 10.3390/rs13030453
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Improvements to Pixel-Based and Object-Based LULC Classification with Auxiliary Datasets from Google Earth Engine

Abstract: The monitoring and assessment of land use/land cover (LULC) change over large areas are significantly important in numerous research areas, such as natural resource protection, sustainable development, and climate change. However, accurately extracting LULC only using the spectral features of satellite images is difficult owing to landscape heterogeneities over large areas. To improve the accuracy of LULC classification, numerous studies have introduced other auxiliary features to the classification model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 60 publications
1
57
0
2
Order By: Relevance
“…The relative superiority of the object-based approach has also been shown when applied to land classification [180,181], such as bamboo mapping [182] or tree classification [183,184]. Nonetheless, even if the object-based methods are generally more accurate, they remain harder to set up because they need to perform a segmentation step (to create the objects) before the classification.…”
Section: Pixel-based and Object-basedmentioning
confidence: 99%
“…The relative superiority of the object-based approach has also been shown when applied to land classification [180,181], such as bamboo mapping [182] or tree classification [183,184]. Nonetheless, even if the object-based methods are generally more accurate, they remain harder to set up because they need to perform a segmentation step (to create the objects) before the classification.…”
Section: Pixel-based and Object-basedmentioning
confidence: 99%
“…In addition to studies that have prepared LULC maps at the global or European scales, a wide range of articles have studied classification methods from pixel-and object-based points of view. Various pixel-based and object-based ML methods [58], semi-automated and automated classification techniques [59], along with different features retrieved from EOs [60], were utilized to generate LULC maps. For instance, Verde et al [48] developed a classification workflow for fine-scale object-based land cover mapping for Greek terrestrial territory by evaluating several classification techniques and strategies for automatic and manual training data extraction.…”
Section: Introductionmentioning
confidence: 99%
“…They found that Sentinel-2 Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and Sentinel-1 VV measurements were the most relevant features to optimize the SVM classifier and achieve higher classification accuracy. In this way, Qu et al [58] investigated the performance of various auxiliary features in improving the accuracy of seven pixel-based and seven object-based RF classification models. Among all RF classification models analyzed by Qu et al [58], the object-based methods showed higher overall accuracy than the pixel-based classification methods, as the best overall accuracy was achieved when the object-based method was used with spectral data only.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [26] carried out fine LULC classification in open-pit mining areas, revealing that MLAs can provide improved classification performance. Qu et al [30] improved the classification accuracy by extracting the soil characteristics and phenological characteristics of the auxiliary dataset from the Google Earth Engine. Yao et al [31] studied the advantages of using continuous multi-angle remote sensing data for classification, attempting to make use of the complementarity of multiangle information.…”
Section: Introductionmentioning
confidence: 99%